Heimat und sozial nachhaltige Landschaftsentwicklung - Kühne, Olaf (Raumforschung und Raumordnung | Spatial Research and Planning, 2011)
Home and regional identity are topics that gain growing and controversial attention in the public and scientific discussion. Frequently home and landscape are understood as distinct objects. On the contrary, both home and landscape here are understood as constitutively socially constructed. Landscape as a social construct represents only one dimension of the social construct of home. Besides, other dimensions of home can be identified: the constitutive dimension of the social, that of well-being, that of time, that of spiritual home and that of marginalization. Crucial for the linkage between the social constructs of home and landscape is the individual acquirement of the construction of a “normal conditioned landscape of home” during processes of socialization. This construction serves as a basis for comparing landscapes as well as it includes a normative expectation of persistence of the socially constructed landscape attributed to physical objects. Due to this social expectation of persistence, changes in the physical structure of landscape are perceived as harassment. However, the target of sustainable development may even demand changes in the structures of physical objects, socially described as landscapes. Therefore the most important challenge of a sustainable development of landscape is to design main physical representatives of home in a way that minimizes the experience of a loss of home.